PELATIHAN DAN PENDAMPINGAN PENULISAN ESAI APLIKASI BEASISWA DAN STUDI LANJUT LUAR NEGERI SECARA DARING - Fandita Tonyka Maharani (Universitas Majalengka, 2021)
Education can be seen as a fundamental aspect in individual’s life. This training and community service has purpose to increase the knowledge about study abroad and scholarship application for the audiences. This community service was conducted online 3 times using Google Meet. The comparison result of pre-test and post-test show that the participants have better motivation and education about studying abroad.